Effect of modified atmosphere packaging and edible wax coating on shelf life of mango - AMULYA P.R NUSAIBA C SREESHA K.R RIFNA E.J; Dr. Sudheer K.P (Guide) (Tavanur 2016 Department of Food and Agricultural Process Engineering)
Effect of modified atmosphere packaging and edible wax coating on shelf life of mango
Effect of modified atmosphere packaging and edible wax coating on shelf life of mango